Gendered Phonetic Variations: Apico-Dental Pronunciation of /t/ and /l/ in Women and Its Sensuality - Dhuha Hadiyansyah; Zaharil Anasy (UPT. Pengembangan Bahasa IAIN Zawiyah Cot Kala Langsa, 2025)
This case study, which employs a qualitative research approach, seeks to explore the reasons behind the pronunciation of the phonemes /t/ and /l/ as apico-dental by some women in both English and Indonesian. The research specifically examines these phonetic variations among 43 second-year students from UAI, who are between the ages of 18 and 20 with a particular focus on how these variations relate to gender. It is significant to spot that the study excludes individuals with speech disorders such as slurred speech or dysarthria, concentrating instead on participants with standard articulatory functions. The participants included 22 students from class IG22A (8 males, 14 females) and 21 from class IG22B (8 males, 13 females). Results revealed that only female participants exhibited apico-dental pronunciation of these phonemes, with no male participants showing this variation. Specifically, six women pronounced /t/ apico-dentally at the end of words like